Physical Violence Against Older Adults: A 7-Year Retrospective Evaluation from a University Hospital’s Department of Forensic Medicine - Abdulkadir Yıldız (Senex: Yaşlılık Çalışmaları Dergisi)
Aim: The present study aims to examine the physical violence inflicted on older adults by strangers and the physical abuse committed by individuals they know; the characteristics of these victims and aggressors; and the physical consequences of violence on victims. The study also compares physical abuse and physical violence inflicted by strangers. Methodology: A total of 156 reports prepared for adults aged 65 years and over who were victims of intentional injury between 2014 and 2020 were retrospectively analysed. Results: Of the cases, 69.9% were male, 66% were subjected to physical violence by individuals they knew or with whom they had a trusting relationship and 34% were subjected to physical violence by strangers. Only 7.7% of older adults reported the violence to judicial authorities themselves. Victims of physical abuse were found to experience revictimization statistically significantly higher than those exposed to stranger violence. Victims of stranger violence were also exposed to statistically significantly more severe injuries than victims of physical abuse. Conclusion: The majority of elder victims were subjected to physical violence by individuals they know or with whom they have a trusting relationship. However, one-third of cases were subjected to violence by strangers according to this study, representing a rate that cannot be ignored. Abuse and violence against older adults remains largely unreported considering their inability to contact judicial authorities or hospitals, or pursue their rights due to physical, economic or mental dependence. Therefore, legal and social measures should be taken to protect older adults.